2017
DOI: 10.1177/1010428317711311
|View full text |Cite
|
Sign up to set email alerts
|

Ferrichrome identified from Lactobacillus casei ATCC334 induces apoptosis through its iron-binding site in gastric cancer cells

Abstract: Ferrichrome is known to be a siderophore, but it was recently identified as a tumor-suppressive molecule derived from Lactobacillus casei ATCC334 ( L. casei). In the present study, we investigated the effects of ferrichrome in gastric cancer cells. Cell lines and xenograft models treated with ferrichrome demonstrated growth suppression. The expression levels of cleaved poly (adenosine diphosphate-ribose) polymerase, and cleaved caspase-9 were increased by ferrichrome treatment. Although the tumor-suppressive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…E. coli Nissle), infections and cancer (e.g. ferrichrome) [7983]. Specifically, the understanding of the antagonistic relationship between siderophores and Lcn2 has allowed these iron-chelators to be utilized for both their canonical and non-canonical functions in various therapeutics.…”
Section: Therapeuticsmentioning
confidence: 99%
“…E. coli Nissle), infections and cancer (e.g. ferrichrome) [7983]. Specifically, the understanding of the antagonistic relationship between siderophores and Lcn2 has allowed these iron-chelators to be utilized for both their canonical and non-canonical functions in various therapeutics.…”
Section: Therapeuticsmentioning
confidence: 99%
“…It has also been reported that an ER-associated molecule, scotin, induced p53 activation under excessive endoplasmic reticulum (ER) stress, thereby inducing cell apoptosis ( 33 ). Our previous studies have reported that ferrichrome upregulated ER stress, leading to the activation of the JNK-DDIT3 pathway, and subsequent induction of apoptosis in colorectal and gastric cancer cells ( 19 , 20 ). Collectively, probiotic-derived ferrichrome is hypothesized to expose cancer cells to ER stress, and thereby induce apoptosis via the activation of ER stress-associated pathways, including JNK-DDIT3 and/or p53, which is a novel mechanism of the antitumor function of probiotic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported that inorganic polyphosphate exhibited tumor-suppressive effects via the activation of ERK (18). Our previous studies also revealed that ferrichrome, identified from L. casei ATCC334, exhibited tumor-suppressive effects in colorectal cancer cells and gastric cancer cells through the induction of DNA damage inducible transcript 3 (DDIT3)-mediated apoptosis (19,20). Ferrichrome was identified as a bacterial iron-chelating agent, as bacteria acquire Fe 3+ from the external environment (21).…”
Section: Introductionmentioning
confidence: 99%
“…Ferrichrome is known as a small high affinity and iron-chelating molecules siderophore, which is created by Lactobacillus casei ATCC334; nowadays, it is regarded as an anti-cancer molecule. Ferrichrome induces apoptosis by activating the c-Jun N-terminal kinase (JNK)-DNA damage-inducible transcript 3 (DDIT3) pathways and upregulating the cleavage of poly adenosine diphosphate-ribose polymerase (PARP) in CRC cells [42]. Ferrichrome is safe for non-cancerous cells, as the growth of IEC-18 and primary cultured cells that belong to the mouse's small intestine are not influenced by it.…”
Section: Ferrichromementioning
confidence: 99%